Abordagens analíticas e técnico-interpretativas na sonata para trompete e piano de Cláudio Santoro - Costa, Radan Soares da (2021)
In this work, analytical procedures are presented that aim to assist the interpreter, providing him with possibilities of resolution about interpretative issues found during the preparation process of the Sonata For Trumpet and Piano by Claudio Santoro as well as the 'translation' of the explicit and implicit elements in the score that are revealed through signs, namely: articulations, dynamics, movements and phrasing. Initially, a survey of works and a bibliographic review was carried out regarding the use of analysis aimed at interpretation. Following the research procedure, we chose the process of applying the analysis script prepared by John Rink presented in the article Analysis and (or?) Performance, as well as the concept described in the work of Nicholas COOK (2006), where the author proposes the vision of the score as “Script” instead of “text”, to be used in that work. In this process, the following aspects were addressed: forms, motifs and melodic elements, dynamics and the realization of a rhythmic reduction of all movements. At the end of this study, we obtained data generated from the analysis carried out, with the aim of using it to suggest alternatives for coherent and conscious interpretation and execution, hoping that these will contribute to future performance of the work.